2012
DOI: 10.1116/1.4757764
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of Al-doped ZnO thin films

Abstract: Articles you may be interested inAtomic layer deposition has been used to fabricate thin films of aluminum-doped ZnO by depositing interspersed layers of ZnO and Al 2 O 3 on borosilicate glass substrates. The growth characteristics of the films have been investigated through x-ray diffraction, x-ray reflection, and x-ray fluorescence measurements, and the efficacy of the Al doping has been evaluated through optical reflectivity and Seebeck coefficient measurements. The Al doping is found to affect the carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…Phase analysis was performed by X‐ray diffraction (XRD) on as‐deposited AZO films at 200°C on borosilicate glass substrates at various Al source temperatures, as shown in Figure 4. The (100)‐oriented wurtzite structure could be found in ALD‐grown AZO films with a deposition temperature range of 200 to 350°C,35–37 and (002)‐oriented AZO films with a deposition temperature range of 150 to 250°C were also reported in the literature 38–40. Moreover, Baji et al41 and Gong et al42 found that the orientation of ALD‐grown AZO film depended on the deposition temperature.…”
Section: Resultsmentioning
confidence: 75%
“…Phase analysis was performed by X‐ray diffraction (XRD) on as‐deposited AZO films at 200°C on borosilicate glass substrates at various Al source temperatures, as shown in Figure 4. The (100)‐oriented wurtzite structure could be found in ALD‐grown AZO films with a deposition temperature range of 200 to 350°C,35–37 and (002)‐oriented AZO films with a deposition temperature range of 150 to 250°C were also reported in the literature 38–40. Moreover, Baji et al41 and Gong et al42 found that the orientation of ALD‐grown AZO film depended on the deposition temperature.…”
Section: Resultsmentioning
confidence: 75%
“…The ALD growth technique can provide good quality film with well-controlled thickness and composition due to its intrinsically self-limiting growth mechanism [7,12]. Given these advantages, Al-doped ZnO films deposited by ALD have been studied in terms of their growth conditions, doping mechanism and their electrical and optical properties [8,9] n simple changes of electrical properties depending on the Al contents and has explained the electrical conducting properties of AZO films by their physical structure and optical properties [3,9,10]. Yet in addition to the physical and optical changes of AZO films, the origins of conducting properties are strongly correlated to the electronic structure of the film, i.e., the band gap, conduction band, and band alignments.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Moreover, the relatively high lattice thermal conductivity of ZnO enables the realization of potentially large gains in thermoelectric performance if it could be reduced. 12,13 Recently, we successfully fabricated inorganic-organic SL structures of Al-doped ZnO and HQ by the combined ALD/MLD technique and demonstrated that the addition of organic layers into the structure of Al-doped ZnO does not result in a notable impairment of the Seebeck coefficient and electrical conductivity of the material; the Seebeck coefficient and resistivity values were -60μV/K and 70 mΩcm, respectively, for a (Zn0.98Al0.02)O sample with a 49:1 inorganic to organic ratio.…”
mentioning
confidence: 99%